2022
DOI: 10.5539/jfr.v11n3p22
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginger Extracts on Palm Olein Quality during Frying and Impact of Fried Oils on Some Biological Parameters of Albino Wistar Rats

Abstract: The objective of this work was to evaluate the effect of ginger root extracts on the oxidative stability of palm olein during frying and to determine the impact of fried oils on some biochemical parameters of albino Wistar rats. The extracts were added to palm olein at concentrations 1000, 1400 and 1800 ppm. A sample containing 200 ppm of butylhydroxytoluene (BHT) served as positive control and another without additives was used as negative one. All oil samples were subjected to 15 frying cycles with samples c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Tis fnding aligns with the work of Womeni et al [27], who found that the rate of decrement in the iodine value of crude soybean oil was higher in the oil without spices than that containing the spices, Z. ofcinale, X. parvifora, M. myristica, A. sativum, and others. Similarly, Loungaing et al [48] observed that the peroxide and anisidine index of palm oleic acid enriched with ginger extract had a signifcantly slower evolution during frying than in the oil sample not containing spices. In the comparative analysis of spices, A. sativum demonstrated the most signifcant efcacy, as evidenced by its lower AUC values relative to P. nigrum and M. myristica across various metrics, including acid, iodine, thiobarbituric acid, peroxide, and anisidine values.…”
Section: Efect Of Stabilizersmentioning
confidence: 85%
“…Tis fnding aligns with the work of Womeni et al [27], who found that the rate of decrement in the iodine value of crude soybean oil was higher in the oil without spices than that containing the spices, Z. ofcinale, X. parvifora, M. myristica, A. sativum, and others. Similarly, Loungaing et al [48] observed that the peroxide and anisidine index of palm oleic acid enriched with ginger extract had a signifcantly slower evolution during frying than in the oil sample not containing spices. In the comparative analysis of spices, A. sativum demonstrated the most signifcant efcacy, as evidenced by its lower AUC values relative to P. nigrum and M. myristica across various metrics, including acid, iodine, thiobarbituric acid, peroxide, and anisidine values.…”
Section: Efect Of Stabilizersmentioning
confidence: 85%